2007
DOI: 10.1111/j.1365-2036.2007.03589.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting survival in patients with advanced oesophageal cancer: a prospective multicentre evaluation

Abstract: SUMMARY BackgroundOesophageal cancer is often diagnosed at an advanced stage, with poor prognosis and severe morbidity. In majority of cases, palliative treatment is the only option available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 30 publications
(46 reference statements)
5
21
1
Order By: Relevance
“…It appears that treatment with radiotherapy alone for elderly patients with esophageal carcinoma is insufficient and there is a need for a more suitable and effective treatment, such as targeted therapy or low-risk chemotherapy. It was confirmed by univariate and multivariate analysis that T, N, M and clinical stage and radiotherapy dose were important prognostic factors for long-term survival, which was consistent with currently available reports (8,9). Of note, we observed that different pathological changes were associated with different survival results.…”
Section: Discussionsupporting
confidence: 79%
“…It appears that treatment with radiotherapy alone for elderly patients with esophageal carcinoma is insufficient and there is a need for a more suitable and effective treatment, such as targeted therapy or low-risk chemotherapy. It was confirmed by univariate and multivariate analysis that T, N, M and clinical stage and radiotherapy dose were important prognostic factors for long-term survival, which was consistent with currently available reports (8,9). Of note, we observed that different pathological changes were associated with different survival results.…”
Section: Discussionsupporting
confidence: 79%
“…These findings have been corroborated in further published studies. 8,14,29,30 Our study demonstrates that SEMS effectively relieves dysphagia. As a one-off palliative procedure, it is important to have low levels of peri-procedural morbidity and minimal re-interventions to maximise quality of life and minimise re-hospitalisation.…”
Section: Discussionmentioning
confidence: 86%
“…Radiotherapy and brachytherapy may provide additional survival benefit over stenting, as well as a more sustained improvement in quality of life 3 . However, esophageal stenting remains a widely accepted intervention for those patients too frail for oncological therapies, or in whom dysphagia has progressed despite treatment 4 .…”
Section: Introductionmentioning
confidence: 99%